EFEKTIFITAS MODEL PEMBELAJARAN JIGSAW II PADA MATERI BARISAN DAN DERET DITINJAU DARI TIPE KEPRIBADIAN SISWA KELAS X SMK MUHAMMADIYAH 3 KLATEN UTARA - Putra, Aji Permana (Intersections, 2022)
The objectives of this research were to find out on the topic of Sequences and Series: (1) which had better learning achievement among cooperative learning Group Jigsaw II or a direct learning; (2) which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students; (3) at each personality types, which had better learning achievement among Jigsaw II or direct learning, and (4) at each learning models, which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students. This research was a quasi-experimental with 2×4 factorial design. The population was all students of SMK Muhammadiyah 3 Klaten Utara on Academic Years 2019/2020. Sampling was done by stratified cluster random sampling technique. The total of sample was 85 students. Statistical tests using the method Lilliefors test for normality, homogeniety of the Bartlett method, anava test with F test (Fisher) and post hoc test using the Scheffe’ method. The significance level was 0,05. Based on hypothesis test, it could be concluded as follows: (1) Jigsaw II had better learning achievement than direct learning,; (2) there were no any differences in the learning achievement in mathematics of the students with melancholies, phlegmatic, sanguine or choleric personality types; (3) in each personality types, the cooperative learning model Jigsaw II had better than direct learning model; (4) in each learning model, the students with melancholies, phlegmatic, sanguine or choleric personality types have the same learning achievement.